HUBUNGAN KONSEP DIRI DENGAN STRATEGI COPING PADA GURU TK SE-KECAMATAN TAMBANG KABUPATEN KAMPAR - Mira Handayani; Ria Novianti; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study was to determine relatonship of self concepts with coping strategies on kindergarten teacher at tambang districk, kampar regency. The population in this study were all kindergarten teachers in Tambang District, Kampar Regency, which were as many as 122 teachers consisting of 33 kindergarten. The sample used is a random sampling the meaning samples were taken randomly, which were as many as 55 teachers. Data collection techniques used were two questionnaires that have been tested for validity and reliability. The data analysis technique uses descriptive analysis and hypotesis testing with statistic chi square. The results of the study indicate that there is a low relationship between understanding the teacher's self concepts and the strategies coping on kindergarten teachers. This is seen from r_ (count) of 0.040. The value of the determinant coefficient obtained is 7,13%, which means self concept has an effecct of 7,13% to coping strategies. Self concept has an effect to emotional focus coping of 14,98%. Self concept has an effect to problem focus coping of 15,76%. It can be concluded that between self concept with emotional focus coping and problem focus coping has a significant relationship. Relationship of self concept with problem focus coping bigger than self concept with emotional focus coping (0,397>0,387). The more positive the self concept, then better coping strategies on that individual.Key Words: Relationships, self concepts, coping strategies.